Changes in Classifications of Chronic Lower-Limb Wound Codes in Patients with Diabetes: ICD-9-CM Versus ICD-10-CM. (February 2015) - Lowe, Jeanne R.; Raugi, Greg; Reiber, Gayle E.; Whitney, JoAnne D.
Abstract : PURPOSE: To enhance the learner's competence with knowledge of changes in classifications of chronic lower limb wound codes from ICD-9-CM to ICD-10-CM in patients with diabetes. TARGET AUDIENCE: This continuing education activity is intended for physicians and nurses with an interest in skin and wound care. OBJECTIVES: After participating in this educational activity, the participant should be better able to: 1. Identify the upcoming transition date and coding differences of ICD-9-CM and ICD-10-CM coding. 2. Interpret the author's study population, methods, and design. 3. Summarize the author's study findings comparing ICD-9-CM coding to ICD-10-CM coding. ABSTRACT: OBJECTIVE: To determine the sensitivity and specificity of International Classification of Diseases, Ninth Edition, Clinical Modification ( ICD-9-CM ) and ICD-10-CM codes for individuals with diabetes and foot ulcers. DESIGN AND METHODS: Wound care providers and researchers are concerned about the potential impacts when the United States transitions from ICD-9-CM to ICD-10-CM . To identify the impact on diabetic foot ulcers, health history and wound variables were prospectively assessed with criterion-standard data from a prospective study of 49 patients with 65 foot ulcer episodes representing 81 incident foot ulcers. The ICD-9-CM and ICD-10-CM code sets were mapped to correctly classify individuals with diabetes and foot ulcers. RESULTS: Frequencies for health history variables were similar in both systems. The ICD-9 code did not capture any data on laterality (left or right) or ulcer depth/severity. The ICD-9 captured 69 of 81 incident ulcers (85%) and 94% of heel and midfoot ulcers, whereas the ICD-10 code captured 78 of 81 incident ulcers (96%) and all incident heel or midfoot ulcers. Sensitivity and specificity for ulcer characteristics were consistently lower in ICD-9 than in ICD-10 . CONCLUSIONS: The ICD-9 and ICD-10 are similar for data capture on health history variables, but wound variables are captured more accurately using ICD-10 . The increased specificity of ICD-10 for ulcer location and severity improves identification and tracking ulcers during an episode of care.